Sculpture par deux. - Musée Rath, Genève (Genève : Musée d'Art et d'Histoire, 1977)
Bucher, André ; Bonnot, François ; Delieutraz, Edouard ; Fornasari, Marc ; Huber, H.R. ; Mazliah, Gilbert ; Meylan, Alexandre ; De Montaigu, Charles ; Moumni-Graber, Sonia ; Schaller, Alain ; Schwarz, Heinz ; Tauss, Michel ; Torres, Manuel ; etc.
Sculpture par deux, Musée Rath, Genève, 22 avril - 30 mai, 1977
boek